TLR4 Inhibition Attenuated LPS‐Induced Proinflammatory Signaling and Cytokine Release in Mouse Hearts and Cardiomyocytes - Christine W. Wiger; Trine Ranheim; Henriette Arnesen; Jarle Vaage; Søren E. Pischke; Arne Yndestad; Kåre‐Olav Stensløkken; May‐Kristin Torp (Immunity, Inflammation and Disease)
ABSTRACT Background Sepsis is associated with myocardial injury and early mortality. The innate immune receptor Toll‐like receptor 4 (TLR4) can recognize pathogen‐associated‐molecular‐patterns (PAMPs) and damage‐associated molecular patterns (DAMPs); the latter are released during tissue injury. We hypothesized that TLR4 inhibition reduces proinflammatory signaling and cytokine release in: (1) LPS or Escherichia coli‐treated isolated mouse heart; (2) LPS‐treated mouse primary adult cardiomyocytes; and (3) the isolated heart during ischemia–reperfusion. Methods Isolated C57BL/6N male mouse hearts were perfused for 120 min, with either LPS, E. coli, with and without CLI‐095 (TLR4 inhibitor). Primary adult mouse cardiomyocytes were treated with LPS or LPS + CLI‐095. Isolated hearts, exposed to 35 min of global ischemia, were treated with either vehicle or CLI‐095 during reperfusion. Infarct size was quantified by triphenyltetrazolium staining. Cytokine expression was analyzed with ELISA, western blot analysis, and qPCR. Results In isolated hearts, E. coli increased the expression of proinflammatory cytokines (IL‐6 and CXCL2), which was not attenuated with TLR4 inhibition. TLR4 inhibition reduced expression (p = 0.004) and release of IL‐6 (p < 0.0001) in LPS‐exposed isolated hearts. LPS activated the nuclear‐factor κ‐light‐chain‐enhancer of activated B cells signaling pathway (NF‐κB) in primary adult cardiomyocytes. Moreover, TLR4 inhibition reduced LPS‐induced mRNA expression and release of IL‐6 in primary adult cardiomyocytes. Isolated hearts treated with CLI‐095 during reperfusion after ischemia (induced DAMPs release) showed reduced infarct size (39 ± 17% to 26 ± 8%, p = 0.034) and decreased IL‐6 release (p = 0.006). Conclusion Inhibition of TLR4 reduced proinflammatory signaling and cytokine release in LPS‐treated and ischemia–reperfused isolated mouse hearts and in primary adult murine cardiomyocytes.